A STUDY ON INTERNET OF THINGS IN FOOD SUPPLY CHAIN'S (International Journal of Food and Nutritional Sciences, 2022)
This essay analyses the Food Supply Chain's (FSC) use of the Internet of Things (IoT) and outlines the system's advantages and disadvantages. Following a review of the literature, six fundamental uses for this kind of network were identified, including those for transportation procurement, food production, resource/waste management, improving food safety, maintaining food quality, and FSC transparency. To accomplish these, clustering is used. According to cluster analysis, researchers should focus more on IoT applications for improving product quality and supply chain transparency, and take into account how IT-based systems can operate seamlessly at every stage of the supply chain.